PENGARUH STRES KERJA, KELELAHAN EMOSIONAL DAN KOMPENSASI TERHADAP INTENTION TO LEAVE KARYAWAN DI PT AIRKON PRATAMA - Waisnayanti, Ni Putu Ayu Liana; Widiastini, Ni Made Ary; Suarmanayasa, I Nengah (Universitas Muhammadiyah Pontianak, 2026)
Employee turnover intention is a major challenge for organizations because it can reduce productivity and increase recruitment costs. This study aims to analyze the effect of job stress, emotional exhaustion, and compensation on employees’ intention to leave at PT Airkon Pratama. This research used a quantitative approach with a survey method involving 87 employees selected through total sampling. Data were collected using questionnaires and analyzed using multiple linear regression with SPSS. The results show that job stress and emotional exhaustion have a positive and significant effect on intention to leave, while compensation has a negative and significant effect. These findings imply that companies should manage work stress and improve compensation systems to reduce employee turnover intention.